A study of pulmonary function test among tea garden factory workers in relation to exposure of tea dust - Das, Birinchi Kartik; Das, Anupi; Choudhury, Biju (International Journal of Research in Medical Sciences, 2017)
Background: Tea is an indispensable beverage used worldwide and brewed from the tea plant Camilia Sinensis. Manufacture of black tea involves several labour intensive processes and the workers involved it are exposed to hazards of inhaling fine tea dust. It has been found that fine tea dust contained fungi such as Manilia, Aspergillus as well as a peculiar streptococcus Chromobacterium. Inhalation of tea dust is known to give rise of both acute and chronic respiratory symptoms, as well as allergic reactions. Methods: The present study is a comparative study among workers working in different sections of the tea factory. A total of 200 male subjects were taken, out of which 100 taken as study group and another 100 taken as control group. All subjects are in the age group of 20—40 yrs. and don’t have any chronic respiratory illness. Pulmonary function tests (PFT) were carried out by using digital Spirometer (Medspiror) and results were recorded in a standard pro forma. Results: The investigator is interested to test whether there were significant differences between parameters of PFT among the study and control group. For this purpose student t test has been applied and significant differences were found in all the parameters of PFT as P < 0.01. Conclusions: Exposure to tea dust affects the lung volumes and flow rates, thereby causing increased prevalence of respiratory, allergic symptoms and significant degree of airway obstruction.